Drawing The Void - Fabricating The Ruined Garden - van Dalen, Jana (School of Architecture, Planning and Geomatics, 2020)
This dissertation questions the process through which subjectivity is transferred into spatial constructs and how singular and collective subjectivities are mediated and constructed through the processes involved in architectural production. It is proposed that architecture is the transfer of subjectivity into the landscape, through re-envisioning the ideological narrative found in “the Garden”, it considers how architecture can be made resiliently within the current state of socio-cultural entropy. Architecture is considered primarily an en-devour through abstraction, the project draws on the garden as an analogous narrative, constructing within its bounds the translations of cultural subjectivity into the landscape, a container of that which is valued and a measure of ideological shifts over time, in itself a stratified ruin, a marked tabula rasa, much like the city. The spatial questions and issues are constructed in parallax, a spatial dialogue between two gardens within the bounds of Cape Town, `the Company Gardens` and the “Void Garden” found in Salt River. The void garden is founded through the processes of parallax as the result of the establishment of the 'Company Garden’. An attempt is made to subvert the subjective fabric which held authority and reposition it in terms of its ideological `other`. The parallax narrative speculates the coming together of various parts in stereoscopic moments of tension, posing a space of question and interference relevant to the current mode of entropy. This entropic parallax space finds its programmatic counterpart in Achille Mbembe’s notion of the Pluriversity1, a space of epistemological and ontological questioning, discovery of alternative methods of knowledge cultural subjectivity production, which is manifested through the projection of diverse epistemic traditions. Following the configuration of parallax superimposition a reconstructed master plan emerged as one stereoscopic moment, providing a multiplied ideological framework of dissonance, to be filled and ruined, as knowledge is reassigned and re-imagined. The architecture embodies a new ideological understanding, a complex network of deepened and multiplied interactions. Envisioned as an armature within which a series of disaggregated programmatic fragments are arranged as a methodology for future architectural speculation to developed. Finally the project manifests as a garden of imminent ruin, as water impedes and the landscape disintegrates, the site is epistemologically disseminated, extending it beyond its bounds.